The Effect of Using Video Learning Media on Student Learning Outcomes in Class IV Science and Science Subjects at SD Negeri 13 AIA Manyuruak South Solok - Karmila, Yesi; Zuliarni, Zuliarni (Lembaga Penelitian dan Pendidikan Mandala, 2023)
The problems found in the field were that some grade IV students at SD Negeri 13 Aia Manyuruak North Solok lacked focus on learning, and the teacher had not used instructional video media in the learning process in science subjects. This research was conducted to determine the effect of using instructional video media on science subjects in class IV SD. The research was carried out using a quasi-experimental quantitative method, using two classes consisting of 15 people in each class. Collecting data using tests in the form of objectives as many as 40 items. Data analysis techniques used are normality test, homogeneity and t test. The research data obtained an average value of the experimental group of 82, higher than the average control group of 70.33. From the t-test analysis, it was obtained that -test > table = with a significant level of 0.05. So, it can be concluded that there is a significant effect on student learning outcomes in the science subject of class IV SD Negeri 13 Aia Manyuruak North Solok